2001
DOI: 10.1128/jvi.75.20.10000-10004.2001
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-Glycine-Aspartic Acid Motif Is Critical for Human Parechovirus 1 Entry

Abstract: The human parechovirus 1 RGD motif in VP1 was studied by mutagenesis. An RGD-to-RGE change gave only revertant viruses with a restored RGD, while deletion of GD was lethal and nonrevertable. Mutations at the ؉1 and ؉2 positions had some effect on growth properties and a ؉1 M-to-P change was lethal. These studies indicate that the RGD motif plays a critical role in infectivity, presumably by interacting with integrins, and that downstream amino acids can have an influence on function.Human parechovirus 1 (HPeV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 52 publications
0
52
0
1
Order By: Relevance
“…S2 C and D). Integrins serve as cell entry receptors for numerous viruses, including the foot and mouth disease virus and several parechoviruses (19)(20)(21). However, the RGD motif is not present in DWV and other iflaviruses.…”
Section: Resultsmentioning
confidence: 99%
“…S2 C and D). Integrins serve as cell entry receptors for numerous viruses, including the foot and mouth disease virus and several parechoviruses (19)(20)(21). However, the RGD motif is not present in DWV and other iflaviruses.…”
Section: Resultsmentioning
confidence: 99%
“…both close to the VP1/2A boundary. It is potentially significant that recombination can occur within the VP1 protein itself, particularly as the RGD motif, which plays a role in receptor binding (Boonyakiat et al, 2001), is located close to the VP1 C terminus and downstream of the putative HPeV4 recombination point. Differences in this region generated through recombination could potentially alter the integrin recognized and thus HPeV biology.…”
Section: Discussionmentioning
confidence: 99%
“…This motif has proven important for HPeV type 1 infectivity, presumably because of interaction with cellular receptors (14). Such a motif is present in all known HPeV strains except type 3, and some researchers have suggested that the latter may use a different receptor for cell entry (3,13).…”
Section: The Studymentioning
confidence: 99%